TAKAYASU ARTERITIS: PATTERN OF CLINICAL AND RADIOLOGICAL FEATURES, EXPERIENCE FROM PAKISTAN - Khan, Asadullah; Asif, Sadia; Haroon, Muhammad; Aslam, Muhammad Zeshan; Shamim, Roshila; ud Din, Zia (Journal of Ayub Medical College Abbottabad, 2021)
Background: Takayasu arteritis (TKA) is a rare large vessel vasculitis occurring in young adults of less than 50 year of age. We analyse the clinical, radiological features, and treatment regimens in Pakistani patients presenting to a tertiary care center. Methods: A retrospective cross-sectional analysis of TKA patients done at the Rheumatology department of Fatima Memorial Hospital. A comprehensive evaluation of clinical, laboratory, radiographic features and treatment regimens was carried out. Results: A consecutive cohort of 18 patients, with 13 patients (72%) of female gender was studied. Mean age of the cohort was 35.94±2.7 years. A mean delay of 2.32±0.43 years between symptoms and final diagnosis was reported, attributed to alternate diagnosis in 57.1% and late presentation in 42.8% cases. Limb claudication (44.4%), absent pulses (38.9%), were the common initial manifestation. Hypertension (61.5%), blood pressure discrepancy between arms (88.9%) and bruit (72.2%) over major vessels were common systemic features. As per angiographic classification, Type V (44.4%), and Type I (33.3%), were most common pattern of disease in the cohort. Subclavian artery (72.2%), renal artery (33.3%), iliofemoral arteries (27.8%), and coronary artery involvement (16.7%) were the common lesions. Coronary artery lesion was higher in females (p=0.52) while renal artery lesion in males (p=0.27). There was no statistically significant difference in involvement of vessels according to gender (p >0.05). Conclusion: Type V and Type I are the common pattern of TKA. Limb claudication was the most common initial manifestation. Renal artery involvement was seen more commonly in males while coronary artery involvement more commonly in females.